2021
DOI: 10.3390/su13052699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Indoor Air Quality and Thermal Comfort of Primary Schools in Winter in a Mediterranean Climate

Abstract: Research studies have shown the potential effects of indoor environmental quality (IEQ) on pupils’ health and academic performance. The COVID-19 pandemic has prompted renewed interest in the assessment of deficient indoor air quality (IAQ) conditions in schools and has become a priority over achieving adequate comfort conditions. Scientific studies confirm aerosols as one of the transmission routes of SARS-CoV-2 so that the possibility of airborne transmission increases in indoor environments with high occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 34 publications
2
48
0
6
Order By: Relevance
“…With the COVID-19 outbreak, humanity has been facing challenges, which have had an impact on every aspect of society, health, economy, culture, etc. Changes due to COVID-19 have also had environmental impacts on air quality and pollution [ 1 , 2 , 3 ], indoor air quality in schools [ 4 , 5 ], energy consumption [ 6 ] and on the built environment [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the COVID-19 outbreak, humanity has been facing challenges, which have had an impact on every aspect of society, health, economy, culture, etc. Changes due to COVID-19 have also had environmental impacts on air quality and pollution [ 1 , 2 , 3 ], indoor air quality in schools [ 4 , 5 ], energy consumption [ 6 ] and on the built environment [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A currently accessible published study on indoor air quality and thermal comfort in the context of COVID-19 in a primary school in a region with a Mediterranean climate [ 4 ] shows that ventilation protocols provide good results in terms of IAQ conditions, but not in relation to IEQ conditions, which are influenced by thermal comfort. The study is based on the analysis of the measured parameters in a new school which used a hybrid model (mechanical and natural ventilation) during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the concentrations of CO 2 decreased around 36% on average due to the COVID pandemic. Furthermore, this study showed that using hybrid ventilation during the pandemic resulted in a decrease of 300 ppm in CO 2 weekly average concentrations and a reduction of 400 ppm with natural ventilation during all school hours (Alonso et al 2021).…”
Section: Indoor Air Qualitymentioning
confidence: 73%
“…Bogdanovica et al [35] analyzed the CO 2 concentration in a secondary school in Latvia, coupling measurement and a pupil survey; they observed an inverse correlation between the CO 2 concentration level and the pupils' performance. The impact of the COVID-19 pandemic measures on thermal comfort and IAQ conditions in Mediterranean classrooms was studied in [36]. The environmental monitoring carried out before and during the pandemic in two classrooms demonstrated that the "emergency" ventilation protocols provided good IAQ conditions with a decrease in CO 2 concentrations; conversely, effects on thermal discomfort conditions were also registered.…”
Section: Introductionmentioning
confidence: 99%